The Enigma Implementation of Predictive Algorithms in Indonesian Legal Perspective - R. Yahdi Ramadani; Steven Liechardo; Audy Danial Wibawanto; Yoga Firdausi (Syiah Kuala Law Journal, 2022)
Predictive Modeling is a statistical technique that can predict future results with the help of historical data and machine learning tools to see if there is a potential for criminal acts in an area using technology. If the Predictive Algorithm is applied to a system in Indonesia, Indonesia must first consider the mechanism for using the system and the risk impact of the system. This research uses normative juridical research. This study uses several approaches, namely the statutory and conceptual approaches. What needs to be considered if this system is implemented in Indonesia is that there is currently no law on personal data, so there are still norms in the regulation of personal data, incomplete regulations regarding Indonesian cyber crime, violations such as the presumption of innocence, and Indonesia must revamp the system. Judiciary in Indonesia, considering there are still areas lacking internet signal. The use of Predictive Algorithms in certain sectors has a good impact. Still, the implementation of Predictive Algorithms in the government sector, especially the Criminal Justice System, violates the human rights of the suspects or suspects related; before the performance of the Predictive Algorithm system, Indonesia must prepare a special law with Personal Data and Reform of the Justice System in Indonesia.